PENGARUH KEADILAN ORGANISASI, TRILOGI KEPEMIMPINAN KI HAJAR DEWANTARA TERHADAP MOTIVASI BERPRESTASI MELALUI LINGKUNGAN KERJA FISIK - Edy Wibowo Susanto; Kusuma Chandra Kirana; Syamsul Hadi (STKIP Persada Khatulistiwa Sintang, 2023)
Teachers must be more than just facilitators in the era of independent learning, they must also be innovators and agents of change. The purpose of this study is the Analysis of the Effects of Organizational Justice, Ki Hajar Dewantara's leadership trilogy on achievement motivation through the physical work environment between public and private school teachers. Methods of data analysis using descriptive and inferential analysis methods. Sampling Technique Simple Random Sampling. Likert Scale Scaling Technique. The analysis used is Patial Least Square, namely variance-based SEM. PLS testing includes: Indicator Tests measured by the criteria: Convergent Validity, Discriminant Validity, and Composite Reliability; and Model Fit Test. The difference test was carried out using an independent sample t-test. Test the hypothesis in the form of an Inner Model or a structural model. The conclusion from this study is that organizational justice has no effect on the achievement motivation of public and private school teachers. Ki Hadjar Dewantara's Leadership Trilogy influences the achievement motivation of Public and Private School Teachers. The physical work environment influences achievement motivation. Organizational justice has no effect on the physical work environment. Ki Hadjar Dewantara's Leadership Trilogy influences the physical work environment. There is no difference in the effect of Organizational Justice, Ki Hajar Dewantara's Leadership Trilogy on Achievement Motivation Through the Physical Work Environment Between Public School Teachers and Private School Teachers